2022
DOI: 10.3389/fpsyg.2022.771598
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Flexible Employment on Workers’ Wellbeing: Evidence From Chinese General Social Survey

Abstract: Based on the 2017 China General Social Survey data, with 5,439 observations as research objects, this paper empirically tests the impact of flexible employment on workers’ wellbeing and introduces labor income as mediator and social security as moderator to explore the mechanism of action. The empirical results show that: flexible employment has an inverted U-shaped relationship with workers’ wellbeing, which indicates that increasing employments’ flexibility will first rise and then reduce their perceived sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In addition, studies suggest the mediating and moderating effect of other factors need to be taken into consideration when examining the impact of informal employment on workers' happiness. Social inequality [32], income [37] and unemployment probability [38] play a mediating role in the relationship between informal employment and subjective wellbeing, while other factors, such as the labor system, can moderate some mediating effect [30]. The study by Liu et al shows that lower labor income reduces the informal workers' happiness, while social security moderates this negative impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, studies suggest the mediating and moderating effect of other factors need to be taken into consideration when examining the impact of informal employment on workers' happiness. Social inequality [32], income [37] and unemployment probability [38] play a mediating role in the relationship between informal employment and subjective wellbeing, while other factors, such as the labor system, can moderate some mediating effect [30]. The study by Liu et al shows that lower labor income reduces the informal workers' happiness, while social security moderates this negative impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings from this study are consistent with prior research on the association between mental health and job flexibility and job security. Increased job flexibility, such as reduced working hours, ability to work from home, or taking off time when needed, in addition to increased job stability have been shown to improve psychological outcomes and decrease anxiety among adults . Our study showed that greater job flexibility and job security were associated with 26% and 25% decreased odds, respectively, of experiencing serious psychological distress and a decrease in feelings of anxiety daily, weekly, and within the past year, indicating the substantive impact that flexible and secure jobs can have on mental health in the short-term and long-term.…”
Section: Discussionmentioning
confidence: 49%
“…Increased job flexibility, such as reduced working hours, 20 ability to work from home, or taking off time when needed, 8 in addition to increased job stability have been shown to improve psychological outcomes and decrease anxiety among adults. [21][22][23] Our study showed that greater job flexibility and job security were associated with 26% and 25% decreased odds, respectively, of experiencing serious psychological distress and a decrease in feelings of anxiety daily, weekly, and within the past year, indicating the substantive impact that flexible and secure jobs can have on mental health in the short-term and long-term. Increased job JAMA Network Open | Occupational Health flexibility and job security can have positive outcomes on employees' mental health for several reasons.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In recent years, the central government intends to reduce social insurance rates as a part of tax and fee reduction policy reform. On the other hand, social insurance, as a part of employee protection, provides employees with long-term benefits and wellbeing (Liu et al, 2022 ). Firms that pay social insurance fees in full amounts are usually in the leading position of corporate governance, employee welfare, and sustainable development.…”
Section: Introductionmentioning
confidence: 99%